KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS CERITA FANTASI SISWA KELAS VII SMP NEGERI 12 PADANG - Nurul Pratiwi Asril; Syahrul Ramadhan (EDU RESEARCH, 2024)
This study aims to determine the correlation between reading comprehension skills and the ability to write fantasy stories among seventh-grade students at SMP Negeri 12 Padang. The research employs a quantitative method with a descriptive correlational approach. The sample consists of 62 students selected using a simple random sampling technique. The research instruments include an objective test to assess reading comprehension skills and a performance test to evaluate students’ ability to write fantasy stories. The results indicate a significant correlation between reading comprehension skills and fantasy story writing skills. The product-moment correlation test shows an r-value of 0.785, meaning there is a positive correlation between the two variables. The findings suggest that the higher a student's reading comprehension skills, the better their ability to write fantasy stories. Thus, enhancing reading comprehension skills can be an effective strategy for improving students’ writing abilities.